Mechanisms of RA action in steroidogenic tissues and pro-apoptotic effects of combined treatment of breast tumoral cell lines with 9-cis retinoic acid and rosiglitazione - Pingitore, Attilio; Bonofiglio, Daniela; Sisci, Diego (My University, 2008)
Vitamin A (Retinol) plays a central role in many essential biological processes such as vision, immunity, reproduction, growth, development, control of cellular proliferation and differentiation. The main active forms of retinol, not primary involved in vision, are alltrans retinoic acid and 9-cis retinoic acid, both able to act at nuclear level by binding their receptors RAR and RXR and modulating many physiological processes. However, the nuclear action of vitamin A derivatives is not the only mechanism of retinoic acid (RA) acting on cells. RA is able to modify covalently proteins via a post-translational modification, named retinoylation that has been shown to occur at physiological concentration on pre-existing proteins and localized mainly in the mitochondrial compartment. The present study has been focused on the non genomic action of RA on steroidogenic tissues, testes and adrenal glands, giving further details on the ability of RA to influence protein activity and therefore cell physiology. In particular RA effects on mitochondria from the adrenal glands and the 2-oxoglutarate carrier protein from testes and TM-3 Leydig cell line were studied, providing new data on the peculiarity of steroidogenic tissues to incorporate RA at dietary levels and demonstrating how the shuttling of reducing equivalent across the mitochondrial membrane is influenced by RA treatment. Looking for the biochemical mechanism of RA action on the Adenine Nucleotide Translocator, that exchanges ATP for ADP between mitochondria and cytosol, for the first time, it was possible to demonstrate how the activity of this carrier protein is positively modulated by the Coenzyme A, a fundamental component of the retynoilating buffer. At pharmacological levels, retinoids are also active compounds in the treatment of cancer due to the capability to promote cell differentiation and their pro-apoptotic activity. In this latter concern, the mechanisms of nutriceutical concentration of 9-cis RA, together with nanomolar concentration of the selective PPARγ ligand, rosiglitazone, to promote apoptosis in breast cancer cell lines, have been investigated. The data lay the basis for a potential use of the combined therapy with low doses of both BRL and 9-cis RA as novel therapeutic tool particularly for breast cancer patients who develop resistance to antiestrogen therapy
Dottorato di Ricerca in: Cellular Biochemistry and Drug Activity in Oncology, Ciclo XXII,a.a. 2008-2009
Keywords: Steroidi; Tumori; Cellule